2009
DOI: 10.1002/pbc.21897
|View full text |Cite
|
Sign up to set email alerts
|

Survival outcome in childhood ALL: Experience from a tertiary care centre in North India

Abstract: The management of ALL requires financial resources and access to quality supportive care. One third of our patients opted for no therapy. The other problem areas were a high proportion of therapy defaulters, lost to follow up and infection related deaths during induction and remission phases. The introduction of remedial measures for resolving the difficulties identified would hopefully improve cure rates in ALL in developing nations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
41
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 39 publications
11
41
1
Order By: Relevance
“…The overall 5-year EFS of 78.7% for our patients was comparable to the 5-year EFS of 75% for patients treated on the CCG-1800 series [6], 76.9% in the TOTAL therapy study 13A at St. Jude Children's Research Hospital [28], and 78% in the BFM 90 [29]. The percentage of patients who relapsed in our study (7.2%) compares favorably with that in many resource-poor countries (17.5%-41.1%) [20,21,30,31]. Our results are similar to those of a recent study from Jordan using St. Jude TOTAL protocols [22].…”
Section: Discussionsupporting
confidence: 73%
“…The overall 5-year EFS of 78.7% for our patients was comparable to the 5-year EFS of 75% for patients treated on the CCG-1800 series [6], 76.9% in the TOTAL therapy study 13A at St. Jude Children's Research Hospital [28], and 78% in the BFM 90 [29]. The percentage of patients who relapsed in our study (7.2%) compares favorably with that in many resource-poor countries (17.5%-41.1%) [20,21,30,31]. Our results are similar to those of a recent study from Jordan using St. Jude TOTAL protocols [22].…”
Section: Discussionsupporting
confidence: 73%
“…But in resource-poor countries like India, limited availability and high cost of Rasburicase hinders its free use. Non-availability and high cost of dialysis is also a big hurdle in managing patients with TLS [9]. Although without a control group, our study cannot conclude that dialysis can be avoided in such patients, it has shown that sevelamer is equally useful in aggressive tumours like Burkitt's lymphoma.…”
Section: Discussionmentioning
confidence: 70%
“…In the developing world induction mortality is high for children with leukemia [9,11]. Sepsis is major barrier to improving outcome but other factors like TLS and hyperphosphatemia add to both morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations